2009
DOI: 10.1007/s00011-009-0026-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age and gender on the striatal astrocytes activation in murine model of Parkinson’s disease

Abstract: The present results provide additional information of potential relevance to understand the mechanisms of gender and age-related difference in susceptibility of nigro-striatal system to MPTP insult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 33 publications
3
23
0
Order By: Relevance
“…Some studies have linked astrocytic proliferation with exposure to toxins and injury in an age and gender dependent manner [68,69]. Miller et al [70] reported that the striatal dopamine depletion and GFAP elevation induced by amphetamines in mice was relatively higher in older animals.…”
Section: Discussionmentioning
confidence: 98%
“…Some studies have linked astrocytic proliferation with exposure to toxins and injury in an age and gender dependent manner [68,69]. Miller et al [70] reported that the striatal dopamine depletion and GFAP elevation induced by amphetamines in mice was relatively higher in older animals.…”
Section: Discussionmentioning
confidence: 98%
“…Glial cells are traditionally known as the support cells for neurons in CNS, but recent studies have shown that their roles in neurodegeneration are not only secondary to neuronal dysfunction. Several previous studies have demonstrated that both astrocytes and microglia were activated under PD conditions, and their roles are very dynamic and cell-type dependent [41][43]. Astrocytes and microglia may exert harmful effects by producing pro-inflammatory and cytotoxic mediators that kill neurons or form scars that barricade axonal regeneration, but in certain circumstances, these cells can turn into highly protective cells, and produce anti-inflammatory cytokines, express and release a panel of pro-survival, neurotrophic and pro-regenerative factors, thereby facilitating neuronal recovery and repair [44][46].…”
Section: Discussionmentioning
confidence: 99%
“…The studies that have been carried out to date appear to support a neuroprotective role for astrocytes in PD. From pathological examinations, an increase in the number of astrocytes as well as in GFAP expression is observed in PD, (Ciesielska et al, 2009;Muramatsu et al, 2003), as with other neurodegenerative disorders. The pathological evidence indirectly indicates that antioxidant pathways might contribute to this neuroprotective effect, because in control brains the density of glutathione-peroxidase-positive cells was higher in the vicinity of the dopaminergic cell groups known to be resistant to the pathological process of PD.…”
Section: Parkinson´s Diseasementioning
confidence: 95%
“…The astrocytic processes construct a bushy network surrounding the injury site, thus secluding the affected part from the rest of the CNS area. Subsequently, astrogliosis has been implicated in the pathogenesis of a variety of chronic neurodegenerative diseases, including Alzheimer's disease (AD), Parkinson's disease, Amyotrophic Lateral Syndrome (ALS ), acute traumatic brain injury, stroke, and neuroinflammatory brain diseases (Axelsson et al, 2011;Ciesielska et al, 2009;Garcia-Matas et al, 2010;Heales et al, 2004;Li et al, 2011;Simpson et al, 2010;Sofroniew, 2000).…”
Section: Oxidative Stress and Neurodegenerationmentioning
confidence: 99%